A C^2 Rational Cubic Ball Interpolant for the Visualization of Shaped Data - Alrawashdeh, Mufda Jameel Abedalhadi; Tahat, Ayser Nasir; Ahmed, Jafar Husni (Discontinuity, Nonlinearity, and Complexity, 2026)
This study investigated the use of a C^2 rational cubic Ball function with four shape parameters to preserve the shape of positive, monotone, and convex data. It was found that by imposing some restrictions on two shape parameters the curve schemes will gain the shape of the data. However, the other two parameters are left free which gives an opportunity to refine the curve schemes as wanted to obtain a visually pleasing curve. The problem of visualization a constrained data is also considered, that when the data is located over a straight line and therefore the curve is required to locate on the same side of the line. Numerical examples and comparisons of the suggested method with other methods are mentioned.